Experiences and results from interdisciplinary collaboration: utilizing qualitative information to formulate disaster risk reduction measures for coastal regions - Martinez, Grit (2019)
This paper illustrates both the potential and challenges of interdisciplinary collaboration amongst researchers from the social sciences/humanities and the natural sciences/engineering in formulating disaster risk reduction measures for coastal regions. The authors aim to share their experiences of working across different scientific and engineering disciplines in the EU project RISC-KIT to co-produce disaster risk reduction measures suitable for specific regional and local contexts, in this case two coastal study areas in Europe (Porto Garibaldi, Italy and Rio Formosa, Portugal). An overview of the historic-cultural origins of scientific disciplines is first presented, explaining the historical fragmentation of scientific knowledge into natural and social sciences and its associated challenges for prior disaster risk studies – and how the current state of an interdisciplinary approach has emerged. This is followed by an analysis of interdisciplinary collaboration, drawing on the experience and data collected (both quantitative and qualitative) from the two case study areas. The article concludes with suggestions to further overcome the segregation of disciplines within disaster risk studies and projects. The authors found that qualitative data help to understand knowledge, values and behaviours of institutional and non-institutional stakeholders in formulating appropriate risk reduction measures to increase resilience in a local context – and that such data work “hand in hand” with quantitative information. Furthermore, the collection of qualitative data by researchers of the natural science and engineering disciplines has the potential to build bridges between disciplines and to stimulate further investigations, as in this case, to explain contradictions in human behaviour when managing risk.